Presence of antibodies to Salmonella in tuatara (Sphenodon punctatus) sera. (August 2015) - Middleton, Danielle M.R.L.; Nelson, Nicola J.; Gartrell, Brett D.; La Flamme, Anne C.
Highlights: Salmonella has not been isolated from tuatara despite being found commonly in their environment. Tuatara sera contained anti- Salmonella antibodies. Some but not all of these antibodies were cross-reactive with E. coli and C. koseri . Antibody responses of captive tuatara to C. koseri but not S . Saintpaul or E. coli were affected by season. The strength of the tuatara immune response is similar or greater than those of exotic reptiles tested, which are known carriers of Salmonella . Abstract: Colonisation of a host by pathogenic microorganisms is a near constant threat to the health of all vertebrates and most species have evolved an efficient adaptive immune response which produces antibodies following exposure to a specific antigen. The strength of this response can be influenced by many factors including sex and season. Tuatara are exposed to Salmonella through contact with infected skinks and soil; however, no gastrointestinal colonisation of tuatara with Salmonella has been found. Using Western blot and flow cytometry we have demonstrated that tuatara possess antibodies which recognise Salmonella antigens, but many of these antibodies are not specific and are cross-reactive with two closely related and ubiquitous bacteria, Escherichia coli and Citrobacter koseri . Our study describes the anti- Salmonella immune responses in tuatara and will help to inform decisions around maintaining wildlife health, as well as providing important insights into the role and development of adaptive immunity in reptilian species.